2016
DOI: 10.1073/pnas.1523930113
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics identify DAB2 as a cardiac developmental regulator that inhibits WNT/β-catenin signaling

Abstract: To reveal the molecular mechanisms involved in cardiac lineage determination and differentiation, we quantified the proteome of human embryonic stem cells (hESCs), cardiac progenitor cells (CPCs), and cardiomyocytes during a time course of directed differentiation by label-free quantitative proteomics. This approach correctly identified known stage-specific markers of cardiomyocyte differentiation, including SRY-box2 (SOX2), GATA binding protein 4 (GATA4), and myosin heavy chain 6 (MYH6). This led us to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…As a result, candidate novel regulators of CM differentiation, for example DAB2, a negative regulator of WNT signaling, are more likely to be true hits. 36 are injected into the mass spectrometer separately ( Figure 3A). Relative changes in the abundance of each protein are estimated by either the area under the curve (AUC) of their peptides' extracted ion chromatograms, or by the number of times the proteins' peptides have been sequenced (spectral counting).…”
Section: Protein and Peptide Separation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, candidate novel regulators of CM differentiation, for example DAB2, a negative regulator of WNT signaling, are more likely to be true hits. 36 are injected into the mass spectrometer separately ( Figure 3A). Relative changes in the abundance of each protein are estimated by either the area under the curve (AUC) of their peptides' extracted ion chromatograms, or by the number of times the proteins' peptides have been sequenced (spectral counting).…”
Section: Protein and Peptide Separation Methodsmentioning
confidence: 99%
“…36 The researchers performed control experiments to ensure that differentiation into CMs was successful, including fluorescence-activated cell sorting for cardiomyocyte troponin to verify that the majority of cells 40 In order to catch the very early phosphorylation signaling events, the samples were analyzed between 0 and 20 min using 2 sets of triple SILAC. This kinetics analysis revealed that phosphorylation occurred as early as 1-5 min ( Figure 4D).…”
Section: Protein and Peptide Separation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of Dab2 in zebrafish embryos through Cas9 mutagenesis resulted in a significant reduction in cardiomyocyte number (Hofsteen et al, 2016), though impact of Dab2 deletion on cardiac development is not notable (Morris et al, 2002b; Moore et al, 2013). …”
Section: Dab2 In the Regulation Of Cellular Signaling Pathwaysmentioning
confidence: 99%
“…Sequential activation and inhibition through both the canonical and the non‐canonical Wnt signalling pathway is critical during the heart development. Inhibition of canonical Wnt signalling could lead to the reduction of the second heart field progenitor cells and affect the differentiation of ES cell into the cardiomyocyte . The non‐canonical Wnt signalling ligands, Wnt5a and Wnt11 express at the anterior pole to the heart tube and play roles during the second heart field migration.…”
Section: Introductionmentioning
confidence: 99%